Forced changes in El Niño–Southern Oscillation due to global warming and the associated uncertainties in ACCESS-ESM1.5 large ensembles - Rashid, Harun A. (Frontiers in Climate, 2022)
Understanding the forced response of El Niño‒Southern Oscillation (ENSO) to future global warming (GW) is important for reliable climate projections; however, many important aspects of this response are yet to be fully understood. Here, we use two large ensembles of CMIP6 historical and SSP3-7.0 experiments (each with 40 ensemble members), performed with ACCESS-ESM1.5, to investigate the combined greenhouse gas (GHG) and aerosol forced changes in selected ENSO properties. We document the forced changes in ENSO’s amplitude, power spectrum, skewness, and feedbacks and quantify the internal variability associated with these forced changes. There is a modest GW-induced increase in the ensemble-mean ENSO amplitude, but a sizable ensemble variation (due to internal variability) with both increases (in 80% of the members) and decreases. To understand the mechanism of this variation, we examine the role of changes in the mean state and atmosphere-ocean coupling processes in the Pacific. We find that the ensemble variation of GW-induced ENSO amplitude changes is most sensitive to the zonal wind forcing change. A change in the zonal gradient of mean sea surface temperatures (SSTs) also plays an important role in the ENSO amplitude change, with the changes in the atmospheric Bjerknes feedback and thermocline feedback playing a minor role. The implications and some caveats of these findings are discussed.